Pengaruh Luxury Brand Perception, Social Influence, Brand Personality Dan Country Of Origin Terhadap Purchase Intention Pada Perusahaan Fast Fashion di Indonesia - Alfina Dwi Juniarti; Rojuaniah Rojuaniah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to take the influence of Luxury Brand Perception, Social Influence, Brand Personality and Country of Origin on Purchase Intention in fast fashion companies in Indonesia. This research is a causal research with a quantitative method approach and using multiple linear regression analysis. The population in this study is the millennial generation who intend to buy fast fashion products at H&M and Uniqlo. The sampling technique using non-probability sampling uses purposive sampling with a total sample of 150 respondents. The results of this study indicate that Luxury Brand Perception has no effect on Purchase Intention, Social Influence has no effect on Purchase Intention, Brand Personality has a positive effect on Purchase Intention, Country of Origin has a positive effect on Purchase Intention.